An Optically‐Pure Hemicryptophane as NMR and ECD Responsive Probe for Chloroform. Issue 10 (7th July 2016) - Brégier, Frédérique; Aubert, Emmanuel; Espinosa, Enrique; Chambron, Jean‐Claude
Abstract: An optically pure hemicryptophane cavitand, in which the primary side of permethylated α‐cyclodextrin (α‐CD) is capped with a C 3 ‐chiral cyclotribenzylene (CTB) derivative, responds to its solution environment, either by electronic circular dichroism or 1 H NMR spectroscopy. In particular, the primary methoxy (6′‐OMe) protons of the α‐CD component behave as solvent sensitive NMR probes. For example, they are more shielded in C2 D2 Cl4 than in CDCl3, and their chemical shifts show opposite temperature dependence. A similar contrasted behavior was observed in benzene vs. toluene, suggesting that the observed effects are related to the size of the solvent molecule. Molecular Dynamics simulations indicated that C2 H2 Cl4 and CHCl3 were included in the α‐CD component of the hemicryptophane, but not in the CTB concavity, with binding energies of –21.1 kJ × mol –1 and –32.7 kJ × mol –1, respectively. Abstract : An optically pure hemicryptophane constructed from PM α‐CDX acts as 1 H NMR and ECD solvent probes, particularly chloroalkanes. The chemical shift of the primary methoxy CDX protons and the cyclotribenzylene‐based ECD are sensitive to these solvents, which, as shown by DFT calculations, are included in the remote CDX cavity.